Minimizing routing overhead using signal strength in multi-hop wireless network - Joshi, Sachidananda S.; Biradar, Sangappa Ramachandra (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Constructing a stabilized route in dynamic topology and decentralized architecture is still an unsolved problem in mobile Ad-hoc networks. There are various research contributions where received signal strength has been used to enhance the routing performance. We reviewed the existing technique and found that adopting the current signal strength-based mechanism is not efficient enough to deal with overhead and energy consumption in mobile Ad-hoc networks (MANETs). The present manuscript introduces a novel routing schema called MROSS or minimizing routing overhead using signal strength (MROSS) that jointly addresses the problems of communication and network lifetime. The outcome of the study was developed using an analytical modeling approach to find MROSS significantly reduces routing overhead and energy consumption in comparison to existing routing techniques in mobile Ad-hoc network.